Facebook Changes in 2013 : The Impact on the Utility of Internet Marketing - Roge, Michał (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The purpose of this study was to investigate the last changes in social media marketing. In particular, the aim was to examine and describe how and why changes, especially in Facebook EdgeRank algorithm, influences marketing activities. Author analyzed changes in Facebook platform which was held in 2012. The information which was gathered could have practical significance. The existing knowledge needs to be brought into the industrial purchasing perspective in the social media market setting.